Konsumsi Daun Bayam untuk Meningkatkan Kadar Hemoglobin Pada Ibu Hamil - Misrawati Misrawati; Nur Asmi; Marliah Marliah (FORIKES, 2022)
Spinach leaves are rich in iron content. The purpose of this study was to determine the effect of consuming spinach leaves on increasing Hb levels in pregnant women at Antang Raya Makassar Health Center. The design of this research was one group pretest-posttest. The research subjects were 15 pregnant women in the second trimester at the Antang Raya Health Center who were selected by purposive sampling technique. Hb level data was measured digitally using the Hemoglobin Testing System Quick-Check. Data were analyzed descriptively followed by paired sample t-test. The results of the analysis showed that the average Hb level of pregnant women before consuming spinach leaves was 2.00 g/dl and after that was 2.67 g/dl. The p value was 0.000 so it can be concluded that there is a difference in Hb levels between before and after consuming spinach leaves.Keywords: spinach leaves; hemoglobin; pregnant mother ABSTRAK Daun bayam kaya akan kandungan zat besi. Tujuan penelitian ini adalah mengetahui pengaruh konsumsi daun bayam terhadap peningkatan kadar Hb pada ibu hamil di Puskesmas Antang Raya Makassar. Rancangan penelitian ini adalah one group pretest-posttest. Subyek penelitian adalah 15 ibu hamil trimester II yang di Puskesmas Antang Raya yang dipilih dengan teknik purposive sampling. Data kadar Hb diukur secara digital menggunakan Hemoglobin Testing System Quick-Check. Data dianalisis secara deskriptif dilanjutkan dengan paired sample t-test. Hasil analisis menunjukkan bahwa rerata kadar Hb ibu hamil sebelum mengonsumsi daun bayam adalah 2,00 g/dl dan sesudahnya adalah 2,67 g/dl. Nilai p adalah 0,000 sehingga disimpulkan bahwa ada perbedaan kadar Hb antara sebelum dan sesudah mengonsumsi daun bayam.Kata kunci: daun bayam; hemoglobin; ibu hamil